Tax Planning Atas Pajak Penghasilan Badan - Dheo Rimbano; Mirra Sri Wahyuni; Eri Triharyati (Owner : Riset dan Jurnal Akuntansi, 2019)
Corporate income tax is a mandatory thing to pay. awareness of paying is still minimal, Islam is more familiar with the term ‘zakat’ than tax (Awareness in paying zakat is very high for Muslims), raising awareness begins with the planning process, so the obstacles in every plan to pay taxes need to be known. The possibility of taxpayers already knowing their obligations, but the meaning is like "double-edged knife", the existence of a trend positivein paying taxes is still to be studied, whether based on the tax amnesty and / or tax planning that starts to run, the negative side of tax amnesty is the fact that Our taxes are categorized as "stubborn" in their discipline of paying taxes. With the existence of tax planning (tax planning) , the taxpayer can save tax that actually exceeds its obligations, and on the other hand help taxpayers in making decisions relating to investment plans in the future. Given the limitations of researchers both in terms of theoretical and technical matters, so that the discussion is clearer, directed and this research does not deviate from the existing problems, the research focus is on the scope of Tax Planning with Law No. 36 of 2008 concerning Income Tax and Tax Regulations other companies in all Commander Companies (CV) in Lubuklinggau City and Bengkulu City.by using qualitative analysis, to analyze tax planning (tax planning) for corporate income tax. then consider the actions that should be taken in streamlining the 2015 owed Corporate Income Tax under Law No. 36 of 2008 article 9 paragraph (1) and Law No. 36 of 2006 article 9 paragraph (1) letter e, activities can be carried out as follows: (1) Provision of health benefits for employees; (2) Providing HR development and education for employees; (3) Provision of bonuses for employee performance; (4) Provision of vehicles for transportation; and (5) giving uniforms to employees. The results of the study show that (1) the Tax Planning of the PPH of the Agency in accordance with the Tax Regulations the majority of the CVs are not implemented and (2) In the financial management of CVs both in Lubuklinggau City and Bengkulu City have not been able to make efficient PPH payments